Antibacterial Activity of Common Spices Extracts on Bacterial Isolates found in Kachhila, a Newari Cuisine (Tribhuvan University Journal of Microbiology, 2020)
Objectives: The objective of this study was to determine the antibacterial property of aqueous extracts of common spices used in the preparation of Kachhila such as garlic, ginger, and turmeric.Methods: After washing and cleaning separately, aqueous extracts were extracted from each spice by crushed with mortar and pestle. Antibacterial activity of aqueous extracts of each spice was evaluated by using agar well diffusion assay and paper disc diffusion assay against test bacteria isolated from buff meat used in Kachhila preparation. Results: Minimum inhibition concentration value of each spice was evaluated against all bacterial isolates. Total bacterial count (CFU/g) of prepared Kachhila was determined in each 30 mins interval up to 150 mins to reveal antibacterial activities of spices used in Kachhila. The antibacterial effect of aqueous extract of garlic extract was found to be the stronger in comparison, followed by turmeric and ginger against test bacterial isolates. The MIC of individual spice extract was found to be 125 to 4000 μl/ml against all the test bacteria. Spices used in Kachhila revealed that bacterial load decreased with time due to the antibacterial property of spices.Conclusion: This study concluded that the antibacterial effect of aqueous extract of Garlic extract was stronger in comparison, followed by Turmeric and Ginger against four test bacteria isolated from buff meat namely; E. coli, Salmonella spp., Pseudomonas spp., Staphylococcus aureus. Therefore this study revealed that spices used in Kachhila have an antibacterial property and enhance the shelf life of Kachhila.